On Some Properties Of Solutions Of A Three-Dimentional Linear Homogeneous System Of Differential Equations With A Anti-Symmetric Matrix - Sahakyan, Georgi
The paper considers the oscillation properties of solutions of a linear homogeneous system of differential equations with an antisymmetric matrix of coefficients. The intermittency of the zeros of the components of the oscillating solutions of the system is proved. В работе рассматриваются осцилляционные свойства решений линейной однородной системы дифференциальных уравнений с антисимметрической матрицей коэффициентов. Доказывается перемежаемость нулей компонент осциллирующих решений системы. Աշխատանքում գործակիցների հակասիմետրիկ մատրիցով գծային համասեռ դիֆերենցիալ հավասարումների համակարգերի համար դիտարկվում են լուծումների օսցիլյացիոն հատկությունները: Ապացուցվում է օսցիլյացվող լուծումների կոմպոնետների զրոների մեկնմիջությունը:
Keywords: Mathematics